Landfill leachate treatment process is transforming and releasing banned per- and polyfluoroalkyl substances to UK water - Neill, Pippa; Megson, David (Frontiers in Water, 2024)
Landfills are a known source of PFAS pollution. Many have environmental permits allowing the discharge of treated leachate to controlled waters. In this article we compared leachate data for 17 PFAS from 17 different landfill sites across the UK. The results show that the landfill leachate treatment process (designed to improve water quality) is generating the banned PFAS; PFOA and PFOS. Approximately 80% of locations tested showed an increase in PFOS, with an increase of 1,335% in one sample. The highest concentrations of PFOS and PFOA in treated leachate were 2,460 ng L−1 and 26,900 ng L−1, respectively. When compared against the environmental quality standard of 0.65 ng L−1 for PFOS this leachate could pose a significant concern. Landfill leachate treatment has proven effective for a wide range of different pollutants, but this research shows in several instances that it is not appropriate for PFAS remediation.